THE MAIN CHARACTERISTICS OF THE SIZE (Academia Science Repository, 2023)
Issues that introduce children to the sizes of objects occupy a certain place in the formation of mathematical ideas. The importance of the size of the object in giving a correct and full characterization of any object is no less important than the importance of its other main characteristics. It is possible to describe the size of the object only on the basis of comparison.